Respons Pembungaan Anggrek Vanda Douglas terhadap Pemupukan KNO3, Aplikasi Sitokinin (Benziladenin dan Thidiazuron), serta Pemotongan Pucuk : Vanda Douglas - Rindang Andam Suri; Yusnita Yusnita; Dwi Hapsoro (Politeknik Negeri Lampung., 2025)
Vanda Douglas orchid is the one of tropical famous plant especially in Indonesia. The beauty of Vanda Douglas orchid is attract people’s attention as an artifial plant, cutting flower, garden decoration and public facility. The aim of research to learn more about : KNO3 fertilization, cytokinin ZPT application which is using Benzyladenine (BA) with or without Thidiazuron (TDZ), detect if there is an interaction or no interaction between application of KNO3 and ZPT cytokinin, also shoot decapitation on the flowering of Vanda Douglas orchids. Research was held in Sanggar Bunga Douglas Kelurahan Sumur Putri, Kecamatan Teluk Betung Utara, Kota Bandar Lampung started from November 2021 to February 2022. First attempt did using a Group Random Design (RAK) with three repetation. The treatment was arranged using factorial 2x5 and the first factor was KNO3 which was K0 (no fertilizer) and K1 (10 g/l of KNO3), and second factor were variant concentrate of BA and TDZ (mg/l) : no ZPT as a control, 200 BA, 400 BA, 200BA+15 TDZ and 400 BA+15 TDZ. Each treatment combination was repeating for three times and every single research consisted of 10 Vanda Douglas orchids and the number of whole plants reach 300 of Vanda Douglas orchids. Second attempt was a factorial research with Group Random Design (RAK) consisted of 2 factor. The first factor was no shoot decapitation (P0) and with shoot decapitation (P1). Second factor were variant concentrate of BA : 0, 200, 400, 200 mg/l + 15 mg/l TDZ, and 400 mg/l + 15 mg/l TDZ. Each treatment combination was repeating for three times and every single research consisted of 10 Vanda Douglas orchids and the number of whole plants reach 300 of Vanda Douglas orchids. Data analyze did by using variant analyze and if showed the significancy, it would continued by BNT test on 5% level. Observation of first attempt started on second week after KNO3 and ZPT sprayed. Observation of second attempt started in week 24 ( or week 12 after shoot decapitation). Variable that observed were : percentage of flowery plant (%) grain length (cm) and number of bud. The result of research showed that combination between KNO3 fertilization and ZPT gave the tiny effect to Vanda Douglas orchid flowering. Application of ZPT (BA or BA+TDZ), shoot decapitation and interaction between both factors was effecting to flowery plant percentage. Only for average of grain length variable and number of bud, the variant analyze did for single factor which was ZPT application. It was caused by no shoot decapitation treatment the whole plants (120 plants) wasn’t flowery. The variant analyze showed that ZPT application had real effect to grain length and bud.